(untitled) (Research, Society and Development, 2021)
Catalytic dehydrogenation of ethylbenzene with steam is the dominant technology for the industrial production of styrene, which is a raw material extensively used in the manufacture of plastics. The commercial catalyst consists of iron oxide doped with potassium and chromium and has a low specific surface area, in addition to being susceptible to deactivation. In order to obtain more efficient catalysts than those available commercially, the effect of the precipitating agent on the performance of iron catalysts, based on hematite, was studied in this work. The samples were prepared by the sol-gel method, using ammonium hydroxide, potassium hydroxide and potassium carbonate as precipitating agents and evaluated in the dehydrogenation of ethylbenzene at 480, 530, 580 and 630 oC. It was observed that the most suitable precipitating agent was potassium carbonate, which produced the most active catalyst, with the highest specific surface area and resistance to reduction. At the temperature of industrial processes (530 oC), this catalyst was four times more active than a commercial sample.